Discordance of Epidermal Growth Factor Receptor Mutation between Brain Metastasis and Primary Non-Small Cell Lung Cancer - Kim, Kyung-Min (Brain Tumor Res Treat, 2019)
BACKGROUND: The aim of this study was to compare epidermal growth factor receptor (EGFR) mutations between non-small cell lung cancer (NSCLC) and corresponding brain metastases (BMs) in Korea society. METHODS: From 2011 to 2016, a total of 74 patients underwent surgical resection of a metastatic brain tumor from NSCLC. Among them, we performed retrospective analysis for 46 patients who underwent EGFR sequencing of primary NSCLC tissues. RESULTS: Among these 46 cases, 18 (39.1%) cases showed EGFR mutation in primary lung cancer. Detected mutation sites were exon 19 (8 cases), exon 21 (6 cases), exon 18 (1 cases), and multiple mutations (3 cases). In 18 cases of BM, EGFR mutation studies were done. Among them, 8 (25.6%) cases showed mutation on exon 19 (5 cases) or exon 21 (3 cases). To compare EGFR mutation status between primary lung cancer and BM, 18 paired tissues from both NSCLC and matched BM were collected. Four (22.5%) patients were discordant for the status of EGFR between primary and metastatic sites. CONCLUSION: EGFR mutations were significantly discordant between primary tumors and corresponding metastases in a significant portion of NSCLC. In treatment of BM of EGFR mutant metastatic NSCLC, due to possibility of discordance, pathologic confirming through brain biopsy is recommended.